Pengaruh Fasilitas Belajar dan Motivasi Belajar Terhadap Prestasi Belajar Peserta Didik Pada Mata Pelajaran IPS di UPTD SDN Wilayah I Kecamatan Bontoa Kabupaten Maros - Ayu Novitasari; Syarifuddin Sida; Muhlis Madani (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2022)
The good learning achievement of a number of students is believed to be the simultaneous influence of the standard of completeness of learning facilities in schools and students' learning motivation. This assumption has resulted in, at least, empirical evidence and different field data sources in several case studies for similar themes, included in this study. Conducted from June to August in class V - UPTD SDN Region 1 Bontoa District, Maros Regency as a locus. This research is an Ex-post facto quantitative study that focuses on the moment of a certain phenomenon that has become a past event to find out both the causal factors and the impact of the event. Proportionate Stratified Random Sampling was used as a sampling technique, where 125 students were randomly assigned in this study according to the Slovin formula. Data collection is done by distributing questionnaires to respondents, namely class V students. The questionnaire uses an inverted number scale with two categories, where the favorable category starts from numbers from 1 to 5 and Unfavorable vice versa (from 5 to 1). In addition to descriptive analysis as one of the mathematical model approaches used in analyzing the relationship between one or several independent variables that are categorical, numeric, or both with one dichotomous categorical dependent variable - logistic regression analysis is also used. Partial tests are included to determine the significance of the effect each independent variable separately, so that it can be seen whether the existing assumptions are acceptable or not. The hypothesis is accepted if t-count t-table or p = 0.05. The results obtained show that learning facilities have a less significant effect on learning achievement. While the motivation variable has a significant influence.